Efeito de um tratamento com auriculoterapia na dor, funcionalidade e mobilidade de adultos com dor lombar crônica - Tolentino, Flora [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Introduction: Low back pain affects much of the world population and may cause, in addition to pain, decrease of functional capacity and lumbar mobility. One way to treat low back pain is the auricular acupuncture technique that uses the ear to treat various diseases. Objectives: To verify if there was a reduction of pain symptoms and increase of the functionality and lumbar mobility in individuals with chronic nonspecific low back pain after having undergone a treatment with auriculartherapy, and see if there was a difference between the intervention performed with needles and seeds. Methods: Randomized clinical trial with participants from 18 to 60 years with chronic nonspecific low back pain for at least three months, of both sexes, divided into three groups, needle (n = 8), seed (n = 8) and control (n = 6). The needle and seed groups received four sessions with auriculartherapy, one per week, all in the same auricular points, and the control group received no intervention until the end of treatment with the experimental groups. For the evaluation of pain variables, functionality and lumbar mobility, it was used in all groups the instruments Visual Analogue Scale, Quebec Back Pain Disability Scale Questionnaire, Sit-to-Stand-Test and Schober Test in the first week and after four weeks. The tests used for data analysis were Two Way ANOVA repeated measures, paired t-test and ANOVA with Bonferroni’s post hoc, with significance level of 5% (p0.05). Results and discussion: It was found that there was a significant difference for the EVA variables (p=0.001), QILQ (p=0.003) and TSP (p=0.033), indicating that there was a decrease in pain and an increase in functionality after treatment in the experimental groups, and no difference was found in the lumbar mobility after treatment. No difference between the treatment carried out with needles and seeds (p=0.641), demonstrating that both treatments were favorable for the reduction of pain without superiority of the two. Conclusion: Auriculotherapy, both with needles and with seeds, is an intervention that has proved beneficial for reduction of chronic low back pain and increasing function in patients with chronic nonspecific low back pain.

Introdução: A lombalgia acomete grande parte da população mundial, podendo provocar, além da dor, diminuição da capacidade funcional e da mobilidade lombar. Uma das formas de tratamento da dor lombar é a auriculoterapia, técnica de acupuntura que utiliza o pavilhão auricular para tratar diversas enfermidades. Objetivos: Verificar se houve diminuição do quadro álgico e aumento da funcionalidade e mobilidade lombar em indivíduos com lombalgia crônica inespecífica após terem sido submetidos a um tratamento com auriculoterapia, além de verificar se houve diferença entre a intervenção realizada com agulhas e sementes. Métodos: Estudo clínico randomizado, com participantes de 18 a 60 anos portadores de dor lombar crônica inespecífica há pelo menos três meses, de ambos os sexos, divididos em três grupos, agulha (n=8), semente (n=8) e controle (n=6). Os grupos agulha e semente receberam quatro sessões com auriculoterapia, uma por semana, todos nos mesmos pontos auriculares, e o grupo controle não recebeu intervenção até o término do tratamento com os grupos experimentais. Para a avaliação das variáveis dor, funcionalidade e mobilidade lombar, foram utilizados em todos os grupos os instrumentos Escala Visual Analógica (EVA), Questionário de incapacidade lombar de Quebec (QILQ), Teste de Sentado para de Pé (TSP) e Teste de Schober, na primeira semana e após quatro semanas. Os testes usados para análise dos dados foram ANOVA Two Way medidas repetidas, Teste t pareado e ANOVA com post hoc de Bonferroni, com nível de significância de 5% (p0,05). Resultados e discussão: Foi verificado que houve uma diferença significativa para as variáveis EVA (p=0,001), QILQ (p=0,003) e TSP (p=0,033), indicando assim que houve uma diminuição na dor e um aumento da funcionalidade após o tratamento nos grupos experimentais, e não foi encontrada diferença na mobilidade lombar após a terapêutica. Não houve diferença entre o tratamento realizado com agulhas e com sementes (p=0,641), o que demonstra que ambos os tratamentos foram favoráveis para a redução da dor, sem superioridade de um dos dois. Conclusão: A auriculoterapia, tanto com agulhas quanto com sementes, é uma intervenção que demonstrou ser benéfica para diminuição da dor lombar crônica e para o aumento da funcionalidade em indivíduos com dor lombar crônica inespecífica.
Effect of a treatment with auriculartherapy in pain, functionality and mobility of adults with chronic low back pain
Keywords: Lombalgia; Acupuntura auricular; Funcionalidade; Movimento; Low back pain; Auricular acupuncture; Functionality; Movement